2018
DOI: 10.23919/cjee.2018.8471285
|View full text |Cite
|
Sign up to set email alerts
|

Active thermal control for delaying maintenance of power electronics converters

Abstract: Several studies have reported about power semiconductors and capacitors being the most sensitive components in power converters. The lifetime of these devices is associated with the mission profile and the resulting temperature profile. For preventing failures, it is of interest to estimate the Remaining Useful Lifetime(RUL) and several condition monitoring methods have been proposed for this purpose. Moreover, modular power converters consist of a high number of components and methods have been proposed to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The effect of power routing on the aging of the ST's ten parallel connected DAB cells is investigated in [89]. The finding from this study is depicted in Figure 24.…”
Section: ) Power Routing In Parallel-connected Modular Convertermentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of power routing on the aging of the ST's ten parallel connected DAB cells is investigated in [89]. The finding from this study is depicted in Figure 24.…”
Section: ) Power Routing In Parallel-connected Modular Convertermentioning
confidence: 97%
“…Figure 24a illustrates the damage sustained by the DAB cells while sharing the power equally for 400 months. The first The impact of power routing on the aging of DAB cells [89] breakdown occurs in the 200th month, and the last occurs in the 370th month, leading to several interruptions in regular operation due to maintenance intervals. However, while the power routing algorithm is implemented, the breakdown of all cells occurs in the 293rd month (Figure 24b), which reduces the maintenance intervals.…”
Section: ) Power Routing In Parallel-connected Modular Convertermentioning
confidence: 99%
“…A study conducted in [72] examined how power routing influences the aging of a set of 10 parallel-connected DAB cells within a smart transformer. Another study conducted by Liserre et al [66] demonstrated the efficacy of power routing in mitigating the thermal cycling effects on the most deteriorated cells within the low-voltage conversion stage of a smart transformer (ST).…”
Section: E Thermal Stress Control At the System Levelmentioning
confidence: 99%